OSTEOPOROSIS TREATMENT ADHERENCE: RESULTS FROM A RETROSPECTIVE COHORT STUDY - O. A. Nikitinskaya; N. V. Toroptsova; E. L. Nasonov (Научно-практическая ревматология)
Treatment adherence in patients with osteoporosis (OP) is rather low throughout the world, and 50 to 75% of patients stop taking anti-osteoporotic drugs within a year after therapy prescription.Objective: to establish determinants that affect patient adherence to OP therapy.Subjects and methods. The investigation enrolled 150 women older than 50 years (mean age, 68.8±9.4 years) with OP duration of ≥3 years who had made an outpatient visit to the V.A. Nasonova Research Institute of Rheumatology. Their examination consisted of a survey using a specially designed questionnaire. Treatment adherence was evaluated, by using the data on the duration of treatment for OP within 3 years prior to the study inclusion, as well as by calculating the drug use index.Results and discussion. During 3 years, 94 (63%) female patients were adherent to OP treatment, including those who took zoledronic acid (78%), denosumab (75%), and alendronate or ibandronate (60%); therapy with antiosteoporotic drugs was changed in 53% of patients. The most common reason for missing or discontinuing treatment was poor drug tolerance (33%); and that for self-replacement of recommended drugs was their cost (75%). Age, education, marital status, income, duration of disease and length of treatment, a familial history of fractures or a hip fracture, the number of concomitant diseases, and the total number of drugs taken did not affect medication adherence. Patients who were more adherent to OP treatment were those who underwent determination of serum vitamin D levels (p=0.009), calculation of a 10-year absolute osteoporotic fracture risk according to the FRAX® algorithm (p=0.022), an annual bone densitometry examination (p=0.0158) and, more often than annually, biochemical blood tests (p=0.0043), as well as those who had visited their physician 3 times or more during the estimated period (p=0.003). There were more people adherent to OP treatment among the patients receiving the parenteral formulations of drugs than among those who took drugs as tablets (p=0.036). Educational materials, brochures, and lectures on OP and a follow-up in a specialized center did not ensure that treatment adherence could be significantly increased (p>0.05).Conclusion. Patient adherence to OP therapy is positively influenced by determination of serum vitamin D levels, calculation of a 10-year absolute osteoporotic fracture risk (FRAX®), annual therapeutic monitoring using bone densitometry and results of biochemical blood tests, regular visits to a physician  who follows up the patient for OP, as well as simplification of a dosing regimen and administration of the parenteral formulations of drugs used to treat OP.